Targeted mutagenesis of BnaSTM leads to abnormal shoot apex development and cotyledon petiole fusion at the seedling stage in Brassica napus L. - Yu, Kaidi; Li, Huailin; Wu, Xiaolong; Amoo, Olalekan; He, Hanzi; Fan, Chuchuan; Zhou, Yongming (Frontiers in Plant Science, 2023)
The Arabidopsis homeodomain transcription factor SHOOT MERISTEMLESS (STM) is crucial for shoot apical meristem (SAM) function, which cooperates with CLAVATA3 (CLV3)/WUSCHEL (WUS) feedback regulation loops to maintain the homeostasis of stem cells in SAM. STM also interacts with the boundary genes to regulate the tissue boundary formation. However, there are still few studies on the function of STM in Brassica napus, an important oil crop. There are two homologs of STM in B. napus (BnaA09g13310D and BnaC09g13580D). In the present study, CRISPR/Cas9 technology was employed to create the stable site-directed single and double mutants of the BnaSTM genes in B. napus. The absence of SAM could be observed only in the BnaSTM double mutants at the mature embryo of seed, indicating that the redundant roles of BnaA09.STM and BnaC09.STM are vital for regulating SAM development. However, different from Arabidopsis, the SAM gradually recovered on the third day after seed germination in Bnastm double mutants, resulting in delayed true leaves development but normal late vegetative and reproductive growth in B. napus. The Bnastm double mutant displayed a fused cotyledon petiole phenotype at the seedling stage, which was similar but not identical to the Atstm in Arabidopsis. Further, transcriptome analysis showed that targeted mutation of BnaSTM caused significant changes for genes involved in the SAM boundary formation (CUC2, CUC3, LBDs). In addition, Bnastm also caused significant changes of a sets of genes related to organogenesis. Our findings reveal that the BnaSTM plays an important yet distinct role during SAM maintenance as compared to Arabidopsis.